(untitled) (Research, Society and Development, 2022)
The changes that took place in the last century gave rise to the “Information Society”. Such a society has been amplified in all sectors of society with Digital Communication Technologies (TDICs). Such innovations arrived in Brazil and, especially in Education, where there is still marked social inequality, regarding the insertion of TDICs in education. Although we have other serious problems that impact on Brazilian learning, such as: school dropout, structural problems, lack of sufficient continuing education for teachers, low salaries, students’ learning deficit, etc., we had a worsening of this scenario with the arrival in March of 2020 of the COVID-19 Pandemic. This work is a mixed qualitative-quantitative research and aims to verify with teachers how teaching mediated by TDICs is happening during the COVID-19 Pandemic at different levels of schooling in Brazil. The results showed that we have advanced a lot in terms of access to new technologies, but it is insufficient in the face of the social inequality that is embedded in our country. It is necessary, among others, public policies that strengthen the training of teachers and the structuring of schools for the use of new technologies.